Case Report: Genetic and immune microenvironmental characteristics of a rectal cancer patient with MSS/PD-L1-negative recurrent hepatopulmonary metastasis who achieved complete remission after treatment with PD-1 inhibitor - Song, Yang; Long, Juan; Su, Xiaona; Chen, Zhuo; He, Yue; Shao, Weikang; Wang, Bin; Chen, Chuan (Frontiers in Immunology, 2023)
Currently, microsatellite high instability (MSI-H)/mismatch repair protein deletion (dMMR) has become a crucial biomarker for utilizing immune checkpoint inhibitors in patients with advanced colorectal cancer (mCRC). However, the proportion of MSI-H/dMMR in advanced patients is only about 5% and mCRC patients with microsatellite stability (MSS)/proficient mismatch repair (pMMR) exhibit poor responses to immunotherapy. Although diverse immune combination therapy regimens have been examined in patients with advanced colorectal cancer who demonstrate MSS/pMMR, these approaches have not yielded favorable efficacy and only a limited proportion of patients have benefited, especially for advanced colorectal cancer patients with liver metastases. Therefore, the mechanism of benefit and potential biomarkers of immunotherapy in patients with MSS/pMMR mCRC deserve more in-depth exploration. Here, we present a case study of a rectal cancer patient with MSS and PD-L1-negative recurrent hepatopulmonary metastases who attained complete remission (CR) and sustained benefits with immunotherapy after systemic therapy had failed. The analysis of the patient's genetic and immune microenvironmental characteristics revealed that mutations in DDR pathway genes and the existence of abundant tumor-infiltrating lymphocytes could contribute to his potential benefit.